Descriptive Qualitative Analysis Based on Physics Mental Model of Students’ Cognitif Understanding on the Concepts of Kinematics Particle and Parabolic Motion - Nyoman Rohadi; Iwan Setiawan; Eko Swistoro (Jurnal Pembelajaran Fisika, 2020)
This article portrays descriptive analysis results based on a physics mental model toward the cognitive reasoning of the first semester students in the year of study 2019/2020 in the physics education study program of the JPMIPA FKIP Bengkulu University on the concepts of kinematics particle and parabolic motion. The analyzed data were a pretest, students worksheets (SWS), and posttest data Of 28 students who participated in basics physics, one class. There was a different score between the mean score of the pretest and the posttest data. The mean score of the pretest data was 45.21 in a range score of 30.00-80.00 and the mean score of the posttest data was 72.50 in a range score of 50.00-100.00. The descriptive analysis of the pretest data and the SWS data indicated that there was a low cognitive competency among the students in understanding the physics diagram and solving physics graphs related problems. But no student found any difficulty in using physics equations on solving the uniform motion problems. Even though some students failed in solving the amount of acceleration related problems. Student’s cognitive reasoning sounds good on the posttest data.   Most of the students could apply the physics mental model on solving conceptual, diagram, graph, and mathematics-related physics problems.Keywords: mental model, cognitive reasoning, arithmetics particle, parabolics motion.DOI: http://dx.doi.org/10.23960/jpf.v8.n1.202012